Preparation of functional copolymer based composite membranes containing graphene oxide showing improved electrochemical properties and fuel cell performance. (25th December 2022) - Pal, Sandip; Choudhury, Arani; Patnaik, Pratyush; Sarkar, Suman; Chatterjee, Uma
Abstract: The objective of this work is to prepare a functional copolymer of poly(acrylonitrile)-co-poly(2-Acrylamido-2-methyl-1-propanesulfonic acid) (PAN-co-PAMPS) and impregnation of graphene oxide (GO) into the copolymer followed by crosslinking to prepare conetwork composite membranes by simple and cost effective solution casting method and evaluating their structural, morphological, thermal, and mechanical properties . The successful incorporation of different amounts of GO content (0.1–1 wt%) within the polymer matrix was confirmed by FT-IR spectroscopy, X-ray diffraction, transmission electron microscopy (TEM), and scanning electron microscopy (SEM). The mechanical properties of the prepared crosslinked composite membranes are found to be greatly enhanced by the addition of GO in the copolymer matrix. The thermogravimetric analysis (TGA) demonstrated considerable improvements in thermal stability for the composite membrane with low GO content. The effect of loading of GO in the copolymer matrix on proton conductivity and fuel cell performance has been studied systematically. The membranes prepared by mixing with 0.5 wt% GO in the copolymer followed by crosslinking exhibited maximum ionic conductivity (K m ), lower methanol permeability (PM ), and higher relative selectivity. This observed PM value is much lower range from 3.02 × 10 −7 to 11.9 × 10 −7  cm 2 /s compared to the Nafion® 117 membrane (22 × 10 −7  cm 2 /s). The fuel cell performance in terms of maximum power density and current density and the durability of the crosslinked composite membranes have also been evaluated here. Low PM, high K m, and high selectivity values show that functional co-polymer/GO crosslinked co-network composite membrane is a promising alternative membrane separator to replace the expensive Nafion® 117 for proton exchange membrane fuel cells (PEMFCs) application. Graphical abstract: Image 1 Highlights: Functional copolymer/GO crosslinked co-network composite membranes were fabricated. The effect of loading of GO on properties and performance was studied. PEMG-0.5 membrane exhibited a maximum power density of 416.6 mW/cm 2 . PEMG-0.5 membrane showed better overall performance than Nafion® 117.